REPRODUCTIVE CROPS IN MULTIFECTED FARMS AND THEIR ROLE IN THE FARM ECONOMY - Ahmedov Ulug‘bek; Kurganov Khakim Rustamovich; Bozorboyev Abduqahhor Abdumannob o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Food security is one of the most important factors in the development of a market economy, solving the problems of social protection and strengthening social stability. Ensuring food security largely depends on the level of development of the agricultural sector, the volume of production, processing conditions, quality of products, storage, agro-technological processes, as well as the level of product stability in the markets.